Exploration of the Causal Roles of Immune Cells and Inflammatory Proteins in Aortic Dissection via Mendelian Randomization - Yueye Chen; Ye Chen; Jingyu Zhu; Jamol Uzokov; Yuemeng Li; Jingming Feng; Ayumi Aurea Miyakawa; Kun Liu; Yanshuo Han (Cardiovascular Innovations and Applications)
Aortic dissection is a life-threatening condition with complex immunological underpinnings. This study was aimed at exploring the causal relationships among immune cells, inflammatory proteins, and aortic dissection, through Mendelian randomization analysis. We used a two-step Mendelian randomization approach to assess potential mediators, focusing on the roles of blood immune cells and inflammatory proteins. We analyzed GWAS data for 731 immune cell traits, 91 inflammatory proteins, and aortic dissection. Single-nucleotide polymorphisms were used as instrumental variables, and analyses were conducted with inverse variance weighting and sensitivity tests to ensure robustness. Our results identified 11 immune cells, including myeloid dendritic cells and monocytes, with significant protective or risk-enhancing effects on aortic dissection. Specifically, CD62L-CD86 + myeloid dendritic cells and CD86 + myeloid dendritic cells demonstrated protective effects, whereas CD14 + CD16 + monocytes were identified as risk factors. Furthermore, the inflammatory protein TRAIL mediated the relationships between specific immune cell types and aortic dissection. Monocyte cell count was identified as a key mediator between myeloid dendritic cells and aortic dissection, thus revealing an immune-mediated pathway that might potentially be targeted for therapeutic intervention. These findings provide new insights into the immunological mechanisms contributing to aortic dissection.